Visual programming languages integrated across the curriculum in elementary school: A two year case study using “Scratch” in five schools - Sáez-López, José-Manuel; Román-González, Marcos; Vázquez-Cano, Esteban (Computers and education, 2016)
Several authors and studies highlight the benefits of the integration of Computer Science into K-12 education. Applications such as Scratch have been demonstrated to be effective in educational environments. The aim of this study is to assess the use of a Visual Programming Language using Scratch in classroom practice, analyzing the outcomes and attitudes of 107 primary school students from 5th to 6th grade in five different schools in Spain. The intervention takes place in two academic years analyzing the practice of integrating coding and visual blocks programming in sciences and arts. The “Computational concepts and computational practices” dimension details a quasi-experimental approach, which showed significant improvement regarding learning programming concepts, logic, and computational practices with an active approach. The “Learning processes and coding in primary education” dimension analyzes the practice of the experimental group through questionnaires and structured observation. In this pedagogical design, students interact and create their own content related to curricular areas with several advantages, such as motivation, fun, commitment, and enthusiasm, showing improvements related to computational thinking and computational practices. Understanding of computational concepts through an active approach, Project Based Learning, usefulness, motivation, and commitment underline the importance and effectiveness of implementing a Visual Programming Language from active methodologies in primary education. Due to the aforementioned benefits and positive results obtained in this research, it is recommended to implement a Visual Programming Language in educational settings in 5th and 6th grade in primary education through a cross-curricular implementation. [Display omitted] •We analyze the use of “Scratch” through statistical inference and case study.•Pretest/posttest design (99%) Active approach and Computational Concepts.•Active Learning, contents in art and History, usefulness and fun.•Possibility of learning sequences, loops, parallelism and events.•Project Based Learning enables an active approach, obtaining high values.